Evaluation of osteogenesis and angiogenesis of icariin loaded on micro/nano hybrid structured hydroxyapatite granules as a local drug delivery system for femoral defect repair. Issue 24 (28th June 2015) - Wu, Yuqiong; Xia, Lunguo; Zhou, Yuning; Ma, Wudi; Zhang, Na; Chang, Jiang; Lin, Kaili; Xu, Yuanjin; Jiang, Xinquan
<x xml:space="preserve">Abstract</x> Icariin has been identified to promote osteogenic differentiation of bone mesenchymal stem cells (BMSCs).